Development of a Psychometric Test: A Care Risk Scale for Homebound Older People With Dementia - Dong, Xiaoxin; Zhao, Lingbo; Kong, Xianbo; Xu, Ting; Sun, Tongda (Frontiers in Psychology, 2022)
Background Homebound older people with dementia (OPWD) face a series of care risks due to disease characteristics, care issues, and the family environment. However, China lacks a quantitative assessment tool for care risk. Thus, we attempted to develop a care risk scale for homebound OPWD. Methods A care risk scale, with initially 18 items, was designed based on a systematic literature review, expert consultation, and a pilot study with 20 OPWD. The initial scale was validated among 1,045 homebound OPWD in Ningbo, China from November 1, 2020 to July 30, 2021. After removing three items that lacked discrimination power, the reliability and validity of the remaining 15 items was evaluated. Factor extraction was performed via principal axis factoring and Cattell’s scree plot analysis, with the resulting factors then being subjected to a varimax rotation. Results The final scale consisted of 15 items assessed on a 5-point Likert scale that loaded on to three different factors, including dementia symptoms (four items), family support (four items), and home environment (seven items). These three factors were found to explain 72.9% of the cumulative variance. The overall Cronbach’s alpha for the final scale was 0.907. The correlation coefficients in the item-to-total analysis ranged from 0.511 to 0.662. Conclusion The validation analysis indicated satisfactory reliability and validity of the 15-item scale for assessing care risk of homebound OPWD. This scale can help long-term care professionals and family caregivers identify care risks and help them take targeted measures to enhance safety of care for OPWD.